Mourner's bench : a novel - Faye, Sanderia (University of Arkansas Press, 2015)
At the First Baptist Church of Maeby, Arkansas, the sins of the child belonged to the parents until the child turned thirteen. Sarah Jones was only eight years old in the summer of 1964, but with her mother Esther Mae on eight prayer lists and flipping around town with the generally mistrusted civil rights organizers, Sarah believed it was time to get baptized and take responsibility for her own sins. That would mean sitting on the mourners bench come revival, waiting for her sign, and then testifying in front of the whole church.